MiR-128-3p Alleviates Spinal Cord Ischemia/Reperfusion Injury Associated Neuroinflammation and Cellular Apoptosis via SP1 Suppression in Rat - Wang, Dan; Chen, Fengshou; Fang, Bo; Zhang, Zaili; Dong, Yan; Tong, Xiangyi; Ma, Hong (Frontiers in Neuroscience, 2020)
Background Neuroinflammation and cellular apoptosis caused by spinal cord ischemia/reperfusion (I/R) injury result in neurological dysfunction. MicroRNAs (miRs) have crucial functions in spinal cord I/R injury pathogenesis according to previous evidences. Herein, whether miR-128-3p contributes to spinal cord I/R injury by regulating specificity protein 1 (SP1) was assessed. Methods A rat model of spinal cord I/R injury was established by occluding the aortic arch for 14 min. Then, miR-128-3p’s interaction with SP1 was detected by dual-luciferase reporter assays. Next, miR-128-3p mimic and inhibitor, as well as adenovirus-delivered shRNA specific for SP1 were injected intrathecally for assessing the effects of miR-128-3p and SP1 on rats with spinal cord I/R injury. SP1, Bax and Bcl-2 expression levels in I/R injured spinal cord tissues were evaluated by Western blotting, while IL-1β, TNF-α, and IL-6 were quantitated by ELISA. Tarlov scores were obtained to detect hind-limb motor function. Evans blue (EB) dye extravasation was utilized to examine blood–spinal cord barrier (BSCB) permeability. Terminal deoxynucleotidyl transferase mediated dUTP nick end labeling (TUNEL) staining was performed for neuronal apoptosis assessment. Results MiR-128-3p expression was decreased, while SP1 amounts were increased in rat spinal cord tissue specimens following I/R. SP1 was identified as a miR-128-3p target and downregulated by miR-128-3p. MiR-128-3p overexpression or SP1 silencing alleviated I/R-induced neuroinflammation and cell apoptosis, and improved Tarlov scores, whereas pretreatment with miR-128-3p inhibitor aggravated the above injuries. Conclusion Overexpression of miR-128-3p protects neurons from neuroinflammation and apoptosis during spinal cord I/R injury partially by downregulating SP1.